Suppression of interdendritic segregation during welding of a 347 austenitic stainless steel pipe reactors. (August 2020) - Ramirez–Ledesma, A.L.; Acosta–Vargas, L.A.; Juarez–Islas, J.A.
Graphical abstract: Highlights: - This work exposed pertinent solutions to several Oil industrial necessities. - Cracks appears in welded pipes of 347 stainless steels used in catalytic reactors. - It was found that cracks are related to interdendritic segregation of weld ribbons. - A model was employed to predict solute segregation avoiding prone failure in 347 SS pipes. Abstract: A study was conducted on "in – situ" gas tungsten arc welded 347 austenitic stainless steel pipes used in a catalytic reactor of a petrochemical plant which eventually failed. Removed parts were studied by using scanning and transmission electron microscopy techniques (SEM, TEM). A complete phase identification was achieved with X – ray diffraction analysis. Microstructural characterization on longitudinally welded paths revealed that cracks started from porosity regions located in welded ribbons and they continue their propagation through the heat affected zone (HAZ) and the base material. The failed welded ribbons microstructure is conformed by gamma columnar dendrites with interdendritic segregation and intermetallic compounds both associated with porosity, altogether inducing a prone failure. To overcome this problem, a constrained solidification dendrite growth model was incorporated in conjunction with the "in – situ" welding of ribbons on 347 SS pipes. Gas tungsten arc welding (GTAW) pipe microstructures were obtained by using the predicted growth velocities (between constitutional supercooling (Vc) and absolute stability (Va) regimes) required to achieve the desire welded ribbons microstructural features. Thus, theoretical predictions exposed the optimal conditions in terms of growth velocities to suppress detrimental features such as interdendritic segregation and crack initiation, aiming welded paths exhibiting segregation – free columnar dendrites and lack of porosity at solidification growth velocities of ≥2.2 × 10 −2 cm/s.